Rigid Yet Resilient: Firms' Margins of Adjustment to Demand Shocks in Regulated Labour Markets - Claudio Lucifora; Federica Origo (Institute of Labor Economics (IZA), 2025)
We investigate how firms adjust to demand shocks when wages and employment determination are regulated. Using firm-level data for the Italian metal engineering industry from 2009 to 2021, we estimate the elasticity of the wage bill to changes in firm's real sales. We disentangle the effect on wage components (base wage and wage cushion) and labour inputs (permanent or temporary employment and working hours). Results show that the elasticity of the wage bill to demand shocks mainly works through adjustment of working hours (especially via short-time work) and partly employment, while wages are less sensitive. Unions at the workplace reduce employment adjustment through a more intensive use of short-time work schemes. The lower employment adjustment to changes in sales in unionized firms does not depend on past investments or innovation, and it is associated to higher responsiveness of profits to declining sales only in weakly unionized firms.
Keywords: J30; J58; C81; 330; labour adjustment; product demand shock; short-time work; unions; collective bargaining